Pengembangan Media Pembelajaran Learning Management System Berbasis Moodle Sebagai Daya Dukung Pembelajaran Fisika - Nisa Nisriana Nurfa; Aripin Aripin; Ernita Susanti (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Utilization of technology can provide convenience in learning for educators and students whom have limited distance and time, to continue to carry out learning activities. One of them is through e-learning. The development and development of e-learning is currently so easy with a learning management system software called Moodle. The purpose of this study was to produce Moodle-based LMS learning media with valid and practical criteria at the Design, Development, and Formative stages. This study uses the Research and Development (R&D) method and the McKenney development model. The Needs and Context Analysis stage was carried out by collecting data through questionnaires, unstructured interviews, literature studies, and field surveys. In the Design, Development, and Formative Evaluation stages, the design framework and features of learning media are designed. The features developed are topics format and enrolled users. The data processing of the needs and practicality questionnaire is carried out using a percentage score, and validity using the validity criterion value. From the results of the needs and context analysis, a learning media is needed that can make students use more than one sense and make students actively participate in learning. The results showed that the validation value was 0.85 with valid criteria and the practicality test obtained a value of 82.1% with practical criteria. Therefore, the Moodle-based LMS learning media that was developed met the valid and practical criteria.